Effects of autonomic nervous system activation on endothelial function in response to acute exercise in hypertensive individuals: study protocol for a randomized double-blind study - Waclawovsky, Gustavo; Boll, Liliana Fortini Cavalheiro; Neto, Salvador Gomes; Irigoyen, Maria Claudia Costa; Lehnen, Alexandre M. (Springer Nature, 2021)
Background: Arterial hypertension has a direct association with endothelial dysfunction and major cardiovascular events. There is evidence showing the benefits of aerobic exercise on flow-mediated dilation (FMD) in hypertensive individuals but little is known about the effect of autonomic nervous system (ANS) activation on FMD of the brachial artery in response to different types of exercise in this specific population. This study aims to examine the effects of ANS activation on FMD of the brachial artery in response to exercise in hypertensive individuals following a session of different types of exercise including aerobic exercise (AE), resistance exercise (RE), or combined exercise (CE). Methods: Thirty-nine hypertensive volunteers aged 35 to 55 years will be randomly assigned to two exercise sessions: AE (40 min on a cycle ergometer at 60% of HR reserve), RE (4 lower limb sets with 12 repetitions at 60% 1-RM for 40 min), or CE (RE for 20 min + AE for 20 min). Each exercise group will be randomized to receive either an α1-adrenergic blocker (doxazosin 0.05 mg/kg−1) or placebo. Ultrasound measurement of FMD is performed 10 min before and 10, 40, and 70 min after exercise. ANS activation is monitored using a Finometer and measurements are taken during 10 min before each FMD assessment. Arterial stiffness is assessed by pulse wave velocity (PWV) analysis using a Complior device. Discussion: We expect to demonstrate the effect of ANS activation on FMD of the brachial artery in hypertensive individuals in response to different types of exercise. This study may give some insight on how to improve exercise prescription for hypertension management. Trial registration: https://clinicaltrials.gov and ID NCT04371757. Registered on May 1, 2020.
Keywords: Aerobic exercise; Autonomic nervous system; Endothelium; Randomized clinical trial; Resistance exercise; Systemic arterial hypertension